2013
DOI: 10.1080/10426914.2013.792409
|View full text |Cite
|
Sign up to set email alerts
|

SU-8-Based Structural Material for Microelectronic Processing Applications

Abstract: This article presents research on the applications of SU-8-based structural material for three different types of semiconductor processing. The processing method using SU-8 as a cost-effective final protection layer replaces the traditional SiN x or SiO 2 thin films in integrated passive devices (IPDs). To evaluate the moisture resistance of the SU-8 films, SU-8 and SiN x are subjected to 1,000 h, 85 C, 85% relative humidity (RH) reverse bias tests and the results are compared. SU-8 is also applied as an isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In was concluded that integration of both rapid prototyping and rapid tooling techniques have been proved to be an efficient way of fabricating micro-featured hot embossing stamps with conformal cooling channels without the use of copper ducts [16]. In addition, the proposed method requires no expensive apparatus compared to methods such as photolithography [17], wire electrical discharge machining [18], focused ion beam [19], electrochemical micromachining [20], deep-reactive ion etching [21], micro machining [22], micro-electro discharge machining [23], laser micromachining [24], lithographie galvanoformung abformung [25], and silicon-based micromachining [26]. However, optimal designs of conformal cooling channels for reducing the cycle time of hot embossing have not been carried out.…”
Section: Resultsmentioning
confidence: 99%
“…In was concluded that integration of both rapid prototyping and rapid tooling techniques have been proved to be an efficient way of fabricating micro-featured hot embossing stamps with conformal cooling channels without the use of copper ducts [16]. In addition, the proposed method requires no expensive apparatus compared to methods such as photolithography [17], wire electrical discharge machining [18], focused ion beam [19], electrochemical micromachining [20], deep-reactive ion etching [21], micro machining [22], micro-electro discharge machining [23], laser micromachining [24], lithographie galvanoformung abformung [25], and silicon-based micromachining [26]. However, optimal designs of conformal cooling channels for reducing the cycle time of hot embossing have not been carried out.…”
Section: Resultsmentioning
confidence: 99%
“…For light propagation, polymer waveguiding structures were considered and, among all, SU-8 was chosen as main material. SU-8 is a versatile, epoxy-based, photosensitive polymer with low electrical conductivity and high optical transparency in the visible spectrum, and is widely used with various micro-electro-mechanical systems (MEMS) [ 21 , 22 ] and microelectronic applications [ 23 , 24 ]. The absorption of light in the ultraviolet (UV) spectrum brings to the possibility of fabricating thin and thick films with high aspect ratios by means of a single UV photolithographic step [ 25 ].…”
Section: Design and Working Principlementioning
confidence: 99%
“…The active microchannel arrays were fabricated from an SU-8 substrate, a flexible photosensitive polymer commonly used in the microelectronics industry because of its versatility and potential for generating high aspect-ratio structures [17]. As a biocompatible polymer [18,19] SU-8 has been extensively explored and used as an implant material for biomedical devices [20].…”
Section: Active Microchannel Electrode Array Fabricationmentioning
confidence: 99%
“…As a biocompatible polymer [18,19] SU-8 has been extensively explored and used as an implant material for biomedical devices [20]. It was employed to fabricate our microchannel arrays, balancing functionality, scalability, and ease-of-use.…”
Section: Active Microchannel Electrode Array Fabricationmentioning
confidence: 99%